Preliminary studies of fungi in the Biebrza National Park (NE Poland). II. Macromycetes - Anna Kujawa (Acta Mycologica, 2013)
This paper presents the second part of the results of the first short-term inventory of fungi species occurring in the Biebrza National Park and is focused on a survey of macrofungi. The total number of macrofungi found during the survey in late August 2012 was 289 taxa: 17 ascomycetes and 272 basidiomycetes, inhabiting diverse ecological niches. The identified fungi belonged to ectomycorrhizal symbionts and saprobionts decomposing wood, plant litter and animal remnants. The identity of 25 mycorrhizal fungi species has been confirmed using molecular techniques. Five species are newly reported for Poland (Amanita olivaceogrisea, Lepiota lepida, Stropharia alcis, Xerocomus fennicus, X. cisalpinus) and 225 taxa (79 %) were not known in the Biebrza National Park. Fifty species are endangered in Poland, of which nine species are protected by law. Data on species richness and the taxonomic diversity of the identified fungi are briefly commented in terms of their significance for nature conservation and future research.